The Function of Pluralism in Traditional Poetry as Language Renewal and Relationship - Dhanu Widi Wijaya; Dini Nur’ainy Gita Saputri (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem : Literature in a truly pluralistic society would serve to represent all the different subcultures, not just the dominant culture. Purpose : This study to explain the function of pluralism as language renewal and kinship through the poetry anthology “Dayak! Dayak! Di manakah kamu?” by Korrie Layun Rampan. Design/methods/approach : This research is a descriptive qualitative research that is embedded in a single case. The source of this research data is a poetry anthology document entitled “Dayak! Dayak! Di manakah kamu?” published by Yrama Widya in 2014. This research data consists of words, phrases, and sentences that contain forms of language pluralism. Purposive sampling is used in sampling. Data collection through library techniques, listen, and record. The data analysis used is heuristic and hermeneutic reading based on semiotic analysis. Findings : The results showed that the function of pluralism as language renewal and kinship includes: 1) acceptance of language order between tribes, 2) implication of language in the realm of tribes/groups, 3) recognition of language diversity, and 4) language maturity as politeness of cultural tribes. Research implications/limitations: The results of this research provide insight into how language exists as renewal and kinship in the context of pluralism. However, this research is limited by its specific scope, which only applies to traditional poetry, which may not be universal in other types of poetry. Originality/value : This research provides an understanding regarding language renewal and kinship which is implied through the “Dayak! Dayak! Di manakah kamu?” by Korrie Layun Rampan as an open system and people can choose to become one language. This condition is considered to be realized in a Dayak society because communities with different languages ​​and cultures are recognized and allowed to participate in controlling language functions.